2015
DOI: 10.2131/jts.40.71
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nicardipine hydrochloride-induced cell injury in human vascular endothelial cells

Abstract: -Nicardipine hydrochloride (NIC), a dihydropyridine calcium-channel blocking agent, has been widely used for the treatment of hypertension. Especially, nicardipine hydrochloride injection is used as first-line therapy for emergency treatment of abnormally high blood pressure. Although NIC has an attractive pharmacological profile, one of the dose-limiting factors of NIC is severe peripheral vascular injury after intravenous injection. The goal of this study was to better understand and thereby reduce NIC-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For example, treatment of human endothelial cells with the endogenous angiogenic inhibitor endostatin induces autophagy as well as cell death, which is insensitive to caspase inhibitors, but is suppressed by the autophagy inhibitor 3-methyladenine 58. Similarly, inhibition of autophagy either by pharmacological inhibitors or by genetic silencing of autophagy-specific genes effectively prevents endothelial cell death triggered by different stressors, including fatty acid overload, 59 simulated ischemia/reperfusion, 52 and the dihydropyridine anti-hypertensive drug nicardipine hydrochloride 60. More interestingly, Chen et al61 have provided evidence showing that in endothelial cells challenged with hypoxia, there is a transition from autophagy-mediated cell survival to autophagy-mediated cell death in a time-dependent manner.…”
mentioning
confidence: 99%
“…For example, treatment of human endothelial cells with the endogenous angiogenic inhibitor endostatin induces autophagy as well as cell death, which is insensitive to caspase inhibitors, but is suppressed by the autophagy inhibitor 3-methyladenine 58. Similarly, inhibition of autophagy either by pharmacological inhibitors or by genetic silencing of autophagy-specific genes effectively prevents endothelial cell death triggered by different stressors, including fatty acid overload, 59 simulated ischemia/reperfusion, 52 and the dihydropyridine anti-hypertensive drug nicardipine hydrochloride 60. More interestingly, Chen et al61 have provided evidence showing that in endothelial cells challenged with hypoxia, there is a transition from autophagy-mediated cell survival to autophagy-mediated cell death in a time-dependent manner.…”
mentioning
confidence: 99%
“…3-MA is a specifi c inhibitor of autophagosome formation via the inhibition of type III phosphatidylinositol 3-kinases (Seglen and Gordon, 1982;Blommaart et al, 1997). These fi ndings demonstrated that autophagy is the main pathway of NIC-induced cell injury, and that inhibition of autophagy could reduce NIC-induced cell death (Ochi et al, 2015). Thus, inhibition of autophagy at the site of injection might reduce NIC-induced vascular injury.…”
Section: Screening Of Protectants Against Nic-induced Endothelial Celmentioning
confidence: 85%
“…Morphological changes and autophagosome stainings of NIC-exposed HMVEC Previously, we determined the NIC-induced increase of autophagosomes with MDC staining (Ochi et al, 2015). To confirm the cytoprotective mechanism of NAC against NIC-induced autophagic cell death, MDC staining was conducted in NIC-treated HMVECs with or without NAC (Fig.…”
Section: Screening Of Protectants Against Nic-induced Endothelial Celmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some instances, excessive autophagy leads to dysregulation of major proteins in VECs, thereby might contribute to the VECs injury and death ( Chau et al, 2003 ; Green and Levine, 2014 ; Gatica et al, 2015 ). More interestingly, VECs challenged with hypoxia, there is a transition from autophagy-mediated cell survival to autophagy-mediated cell death in a time-dependent manner ( Ochi et al, 2015 ). The beneficial effects of autophagy in VECs are likely to be context-dependent, since autophagy may also contribute to cell death under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%